Pengaruh Penambahan Asam Oleat terhadap Karakteristik Nanopartikel Magnetit dengan Metode Kopresipitasi - Della Damayanti; Ridwan Yusuf Lubis; Abdul Halim Daulay (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study discusses the use of natural iron sand in the manufacture of magnetite nanoparticles with oleic acid. The purpose of the study is to produce nano-sized magnetite as an alternative photocatalyst material. Magnetite nanoparticles were synthesized with variations of oleic acid (0.75 ml, 1.5 ml, 2.25 ml, 3 ml) and the addition of 7.5 ml of diethylamine. Synthesis was carried out using XRF to determine the elements contained in the iron sand, SEM to determine the surface morphology, and UV-Vis to determine the size of the bandgap. The results showed that increasing the oleic acid content significantly increased agglomeration due to the large number of particles that merged with each other, while increasing the bandgap value. The results showed that the addition of oleic acid had an effect on the iron sand. The highest XRF test of 88.234% was obtained in the iron sand sample before processing, the lowest SEM test was 0.9 μm, and the highest UV-Vis test was 2.644 eV indicating an increase in the bandgap energy value due to the role of oleic acid as a surfactant. The novelty of this research lies in the use of natural iron sand combined with a fixed proportion of oleic acid (up to 3 ml) and diethylamine (7.5 ml). A good bandgap for the photocatalyst is 2.638 eV which is influenced by the addition of oleic acid as a surfactant. These magnetite nanoparticles show optimal potential and characteristics as photocatalyst materials.